Satisfaction with the quality of stroke care in the Russian Federation and the People's Republic of China - S. S. Yu (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
This study focuses on comparing and analyzing the satisfaction of quality of medical care for patients with acute stroke in the Russian Federation (RF) and the People’s Republic of China (PRC) to identify major problems and the most successful organizational solutions in the system of medical care for patients with stroke. The analysis of differences was performed by the following parameters: quality of care in hospital assessed by patients; the attitude of the medical and nursing staff and the physician to patients (assessed by patients); timely diagnosis and treatment; the level of staff qualifications assessed by patients; satisfaction with the outcome of treatment; availability and volume of conversations held with the patient about the nature and causes of the disease; test results by the life quality scale EQ-5D.